MATERIALS ON THE GENEALOGY OF THE HEREDETARY MUSLIM NOBILITY OF DERBENT - Ajtberov, Timirlan Magomedovic (History, Archeology and Ethnography of the Caucasus, 2025)
This article offers a novel and in-depth analysis of the structure of the hereditary Muslim nobility in Derbent during the latter half of the 18th century, one of the two principal cities within the East Caucasian khanate that emerged following the dissolution of the Iranian Afsharid Empire. This study introduces into scholarly discourse a previously unknown 18th-century Arabic manuscript, preserved in its original form, which the author has titled “The List of Seyids of the City of Derbent” based on its content. Through examination of this list, alongside a related Russian archival document published as an appendix and entitled “Aghamirs and Mullahs,” as well as other relevant Arabic sources on the history of Derbent, such as the “Message of Agamir Muhammad-Kazi of Derbent to Kadi-Said Usishinsky (late 18th century)”, several key conclusions have been reached. While the presence of descendants of the Prophet Muhammad in Derbent is documented from the pre-Mongol period, this specific category of Muslim nobility persisted during the Khanate era (18th century), although distinct branches had become geographically dispersed by this time. In contrast to the Kazikumukh descendants of the Prophet, who were classified as sharifs, the Derbent lineage held the status of Seyids according to Muslim jurisprudence. These Seyids enjoyed privileges under the Dagestani Shi’ite khans, notably receiving a portion of the annual revenue from ancient waqf endowments. The analysis of the “List” suggests that this privileged status led to attempts by external individuals to integrate into the Seyid community, a phenomenon resisted by the townspeople who, in part, invoked the authority of the khanate.
Keywords: Sheihali-khan; Armenians; Quba; khanate; Lezgins; Derbent; Turkic people; Güney; Kabir; seyids